A Mini Review on pH-Sensitive Photoluminescence in Carbon Nanodots - Liu, Cui; Zhang, Fang; Hu, Jiao; Gao, Wenhui; Zhang, Mingzhen (Frontiers in Chemistry, 2021)
Carbon nanodots (C-dots) with sp2/sp3 framework and diameter of less than 10 nm contain abundant functional groups or polymers on their surface. C-dots have attracted immense attention due to their unique optical properties, excellent biocompatibility, facile preparation and low cost. With these merits, C-dots have been used in a wide range of applications including sensing, bioimaging, catalysis, and light-emitting devices. C-dots exhibit good optical properties, such as tunable emission wavelength, good photostability, non-blinking, up-conversion emission, etc. Of note, C-dots show intrinsic pH-sensitive photoluminescence (PL), indicating their great potential for pH sensing, especially in intracellular pH sensing. In this review, we systematically summarize the pH-sensitive PL properties, the pH-sensitive PL mechanism, as well as recent research progress of C-dots in pH sensing. The current challenges of pH-sensitive C-dots and their future research focus are also proposed here. We anticipate this review might be of great significance for understanding the characteristics of pH-sensitive C-dots and the development of photoluminescent nanomaterials with pH-sensitive properties.